From upgrade to uptake: The effect of mobile internet infrastructure on usage of local online services - Constantin Mang (International Telecommunications Society (ITS), 2013)
This paper provides evidence that superior mobile Internet infrastructure increases take-up of location-based online services. Using data from the largest German online platform for restaurant reviews, I find that upgrading the 2G network to 3G increases the number of restaurant reviews and the share of reviews written on smartphones. To identify the causal effect of the network upgrade, I exploit the geographic location of restaurants relative to cellular network antennas and the terrain around them. Since the 3G signal is much more dependent on a clear line-of-sight than the 2G signal, some restaurants that were previously well covered by 2G are blocked from 3G reception due to geographic obstacles such as hills and forests.
Keywords: L86; R42; H54; 330; Mobile Internet; infrastructure upgrade; broadband